2014
DOI: 10.3892/mco.2014.296
|View full text |Cite
|
Sign up to set email alerts
|

Association between vascular endothelial growth factor gene polymorphisms and bladder cancer risk

Abstract: Abstract. Vascular endothelial growth factor (VEGF) gene polymorphisms are associated with susceptibility to a number of cancers. The present case-controlled study aimed to investigate the correlation between VEGF gene polymorphisms and the risk of bladder cancer. The effects of VEGF polymorphisms were investigated in patients with bladder cancer and healthy controls in our hospital between May, 2008 and May, 2013. Peripheral blood samples were obtained from 480 patients with bladder cancer and 420 healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Certain polymorphisms have been identified in the VEGF gene. In order to evaluate the association between the VEGF polymorphism with the various types of cancer risk, numerous molecular epidemiological studies have been performed in different populations recently (6). However, there were no clear conclusions due to inconsistent statistical results.…”
Section: Introductionmentioning
confidence: 99%
“…Certain polymorphisms have been identified in the VEGF gene. In order to evaluate the association between the VEGF polymorphism with the various types of cancer risk, numerous molecular epidemiological studies have been performed in different populations recently (6). However, there were no clear conclusions due to inconsistent statistical results.…”
Section: Introductionmentioning
confidence: 99%
“…There are over 30 variants in VEGF; three of the common polymorphisms in the VEGF gene can influence gene expression and alter the function of the protein, including -634G/C, +936C/T, and +1612G/A (Watson et al, 2000;Ruggiero et al, 2011). VEGF -634G/C, +936C/T, and +1612G/A are reported to have a role in VEGF protein synthesis and in the development of several kinds of cancers Dong-Ju et al, 2014;Lau et al, 2014;Rahoui et al, 2014;Yang et al, 2014b;Yu et al, 2014). Only one previous study has reported an association between VEGF polymorphisms and the development of osteosarcoma .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, these polymorphisms may affect VEGF protein concentrations influencing the angiogenesis process and may be related to inter individual variations in tumor risk, progression, and prognosis. In recent years, the VEGF SNPs have been reported to be associated with cancers of the lung [20], colorectum [21], breast, and bladder [2223]. Moreover, the VEGF SNPs have also been reported to be associated with clinical outcome of esophageal cancer, renal cell carcinoma and non-small cell lung cancer [2426].…”
Section: Introductionmentioning
confidence: 99%